Re-creation and historicity through the modernist sieve: Casa de Huespedes Ilustres by Rogelio Salmona (2021)
This text elaborates and brings up-to-date ideas on the processes of place-making and recreation in architecture (Rueda, 2009), with a study on the Casa de Huéspedes Ilustres in Cartagena de Indias (1980-1982) by architect Rogelio Salmona (1927- 2007). One initial premise is place-making, a re-creative process that entails the transformation of an existing site, which holds itself to a potential for poetic interpretation that, works to elevate the architect to the dimension of a dwelling construct of historicity. Historicity is understood here as the immanence of the past, of time and history in the making of our present and the imagination of our future. It is stressed here that historicity paradoxically attempts for an ahistorical expression of eternity in time. The concept of place, which exceeds in its complexity, and includes that of site, unfolds into larger totalities to configure our “place-world.” Place and world in the phenomenological tradition are synonymous (Merlau-Ponty, 2004, p. 196, xi, pp. 405-407; Malpas, 1999, p. 196; Rueda, 2015, pp. 19-46). Place-making is understood therefore as poetic recreation: union, condensation or transfiguration of –material, experiencial, and memorable– architectural images coming from other places in the configuration of a world or totality of experience.